Validitas Dan Praktikalitas Modul Ajar Sistem Instalasi Tata Udara Berbasis Kompetensi Abad 21 - Muhammad Fauzi; Ayu Hendra (Journal of Electrical Vocational Education, 2025)
The limited availability of standardized teaching materials is an obstacle to practical learning of air conditioning installation systems at SMK Negeri 5 Padang. Although AC trainers are available, students do not yet have complete, systematic, and industry-standard practice guides. This study aims to develop and determine the validity and practicality of a 21st-century competency-based air conditioning installation system teaching module to support learning in SMK. The study uses a Research and Development (R&D) approach with a focus on two aspects: validity and product practicality. The development model used is 4D (Define, Design, Develop, Disseminate), with an emphasis on the Develop stage for feasibility testing. The Disseminate stage was carried out in a limited manner through a trial at SMK Negeri 5 Padang due to time constraints. The research procedures included needs analysis, module and jobsheet design, validation by material and media experts, and practicality testing by teachers and students. The validation results showed that the module met the criteria for content feasibility, appearance, language, and conformity to 21st-century learning principles, thus being declared valid. The practicality test also demonstrated that the module is easy to use, follows a practical flow, and supports the achievement of learning objectives, making it highly practical. Each worksheet includes a 4C-based assessment rubric to help teachers objectively evaluate learning outcomes. Therefore, this teaching module is deemed valid, practical, and suitable for use in refrigeration and air conditioning engineering lessons at vocational schools.